PENYULUHAN PEMANFAATAN TEH DAUN GENDOLA (Basella alba L.) SEBAGAI MINUMAN KESEHATAN KEPADA KELOMPOK MAJELIS TAKLIM Al-MUSAFIRIN KOTA BENGKULU - Gina Lestari; Ade Septianti; Anggun Oktaviana; Dinita Lailatul Wahida; Feby Sintia Dewi; Fitria Rahmadani; Hesni Tria Wulandari; Rangga Putra Merdi; Rafif Nugraha; Reffi Tri Andayani; Yolanda Prenty (Sekolah Tinggi Ilmu Kesehatan IKIFA, 2024)
Gendola leaves are widely used as a traditional medicine for appendicitis, dysentery, influenza, bladder inflammation, measles and chicken pox, bruises, gout and hemorrhoids, healing internal and external wounds after surgery and anti-diabetic. Community service was carried out at the Al-Musafirin religious study assembly in Bengkulu City. The aim of this PkM is to provide education and knowledge to the women of the Al-Musafirin study taklim assembly about the benefits of gendola herbal tea leaves. The method used in this PkM activity is counseling to the group of recitation women at the Al-Musafirin mosque, which begins with how to make gendola herbal tea leaves, namely the ingredients for making herbal tea: Tea casings, Dried Gendola (Basella alba L) leaves 5 g , Dried jasmine flowers 25 g and how to serve gendola leaf herbal tea and its benefits. The results of this community service activity are a form of sharing knowledge from lecturers and students of STIKES Al-Fatah Bengkulu to the Al-Musafirin study group in Bengkulu City. This community service activity provides insight and knowledge to the community